Interdisciplinary Assessment of Hygiene Practices in Multiple Locations: Implications for COVID-19 Pandemic Preparedness in Vietnam - Nguyen, Trang Huyen Thi; Le, Huong Thi; Le, Xuan Thi Thanh; Do, Toan Thanh Thi; Ngo, Toan Van; Phan, Hai Thanh; Vu, Giang Thu; Nguyen, Tu Huu; Phung, Dung Tri; Nghiem, Son Hong; Vu, Thuc Minh Thi; Nguyen, Thu Ha; et al. (Frontiers in Public Health, 2021)
Vietnam was facing the risk of the COVID-19 pandemic due to the shared border with China, at the early stage of the outbreak. The hygiene practice was considered as an effective prevention method. However, there is minimal data on hygiene practice against pandemic at the community level. Thus, this study aimed to assess the hygiene practice in society by using a community-based survey. A cross-sectional study was conducted based on survey monkey from December of 2019 to February of 2020. The Snowball sampling technique was used to recruit participants and the exploratory factor analysis was applied to scrutinize the construct validity of the measurement. We used the Tobit regression model to assess the association between related factors and hygiene practice. Hygiene in a high-risk environment and Hygiene in the social and educational environment were two main factors after applying the EFA method. Participants grade the community sanitation practice quite low (around 6 out of 10). Besides, the mean score of hygiene practice at a local level in a high-risk environment was slightly low at 6.0. The score of sanitation in the Central region (5.3) was quite low compared to the North (5.8) and the South (6.2). The most high-risk environment was construction, industrial zone and food safety. Our study gives an insight into the pandemic preparedness at the grassroots level. The finding suggested the necessity of specific communication education for society to improve the compliance of hygiene practices to prevent the spreading of COVID-19.